Персоналізований підхід до налаштування функціоналу в e-commerce системі для власників тварин - Константинов, Б. С. (ХНУРЕ, 2024)
In response to the challenges posed by modern lifestyles and the potential neglect of pet care duties, this paper proposes the development of an electronic commerce system tailored to assist pet owners. Drawing upon insights regarding the impact of neglect on pets' well-being and the need for convenient management tools, the proposed system aims to streamline pet care responsibilities. By offering personalized product filtering, users can easily find items tailored to their pets' specific needs, saving time and ensuring optimal care. Additionally, the system's reminder creation feature not only facilitates timely task completion but also fosters a proactive approach to pet care, enhancing overall pet welfare.
Keywords: інтерфейс користувача; персоналізовані рекомендації; база даних товарів; управління замовленнями; профілі користувачів